2021
DOI: 10.3390/su13136991
|View full text |Cite
|
Sign up to set email alerts
|

Actions to Promote the Employment and Social Inclusion of Muslim Women Who Wear the Hijab in Catalonia (Spain)

Abstract: The current context of growing religious and cultural diversity requires, from societies, an adequate management of the expression of religious diversity in different social spheres, including the workplace. Muslim women who wear the hijab are one of the social groups that most frequently suffer prejudice and discrimination in work settings due to the intersection of multiple forms of discrimination, including gender, ethnic origin, religion and the use of a visible religious symbol. With the aim of exploring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…These results corroborate Heliot et al's (2020) findings, who found religion brings more benefits to organizations and more of them can be enhanced by favoring inclusion as opposed to focus on the potential conflicts and tensions. This systematic review is focused on the period before July 2020, when the systematic review was finalized, but more research was developed later (Garcia- Yeste et al 2021). Further scientific literature reviews could identify more actions and strategies that have a positive impact on building more inclusive workplaces for all.…”
Section: Discussionmentioning
confidence: 99%
“…These results corroborate Heliot et al's (2020) findings, who found religion brings more benefits to organizations and more of them can be enhanced by favoring inclusion as opposed to focus on the potential conflicts and tensions. This systematic review is focused on the period before July 2020, when the systematic review was finalized, but more research was developed later (Garcia- Yeste et al 2021). Further scientific literature reviews could identify more actions and strategies that have a positive impact on building more inclusive workplaces for all.…”
Section: Discussionmentioning
confidence: 99%